Macroeconomic determinants of exit from aid-dependence - Degol Hailu; Admasu Shiferaw (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
This paper analyses macroeconomic aspects of exit from aid-dependence. By 'exit from aid', we mean substantial and enduring decline over time in Official Development Assistance (ODA) as a share of Gross Domestic Product (GDP). The relevant macroeconomic variables are identified by systematically comparing two groups of countries. These are countries that initially had similar and very high degrees of dependence on international aid but followed dramatically different trajectories of aid-dependence afterwards. This comparison was carried out over five decades since the 1960s using both non-parametric and parametric approaches. We find that the likelihood of exit from aid increases significantly with macroeconomic stability in the sense of maintaining moderate inflation, the rate of investment; aggressive effort at domestic resource mobilisation; and structural change in favour of a growing industrial sector, particularly manufacturing. We conclude that if donors and recipients were to coordinate their aid efforts to support the above-mentioned policy objectives, aid could still be a development tool with diminishing importance.
Keywords: E2; F13; F35; O1; O11; O14; O16; 330; macroeconomic policy; foreign aid; economic growth; investment; savings; inflation; exports; manufacturing; Entwicklungshilfe; Wirtschaftswachstum; Wirtschaftspolitik